1979
DOI: 10.1002/1097-0142(197908)44:2<446::aid-cncr2820440211>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Radical radiation therapy of advanced lung cancer. Evaluation of prognostic factors and results of continuous and split course treatment

Abstract: One hundred patients with inoperable (80) or unresectable (20) bronchogenic carcinoma without evidence of spread beyond the thorax and supraclavicular nodes were planned for radical radiotherapy. Seventy-six patients received continuous irradiation (6000 rads in 30 treatments in 6 weeks, TDF 99) and 24 received split course therapy (2 courses of 2500 rads in 10 treatments with a 3 week break between courses, TDF 88). Forty-three patients had squamous cell carcinoma or adenocarcinoma and were considered to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The SEER registry does not collect data regarding chemotherapy 21. However, past and current treatment practices in the United States suggest that most patients who are treated with adjuvant EBRT also receive chemotherapy 10, 13, 26, 27, 29–31. It is plausible that the survival advantage in our study may be the result of treatment with adjuvant chemotherapy rather than EBRT.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The SEER registry does not collect data regarding chemotherapy 21. However, past and current treatment practices in the United States suggest that most patients who are treated with adjuvant EBRT also receive chemotherapy 10, 13, 26, 27, 29–31. It is plausible that the survival advantage in our study may be the result of treatment with adjuvant chemotherapy rather than EBRT.…”
Section: Discussionmentioning
confidence: 92%
“…Most centers in the United States employ a continuous course of EBRT with total doses from 45 Gy to 54 Gy in fractions from 1.8 Gy to 2 Gy 16, 26. Although this regimen has not been investigated in a randomized study for pancreatic cancer, it has been shown to be more effective radiobiologically in other malignancies than a moderate‐dose, split‐course regimen 27. Additional methodological concerns regarding the delivery of radiation therapy remain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no significant differences were found in response, duration of response, survival, or toxicity between split‐ and short‐course radiotherapy 10 . Many other studies have shown that split‐course CRT, while reducing radiotherapy‐related toxicity, may in turn lead to impaired LC rates 11–19 . The prolongation of the total treatment time may cause an accelerated repopulation effect, leading to a decrease in the LC rate of malignancies, such as head and neck, bladder, and cervical cancers 20–22 .…”
Section: The Concept Of Split‐course Radiotherapymentioning
confidence: 98%
“…10 Many other studies have shown that split-course CRT, while reducing radiotherapy-related toxicity, may in turn lead to impaired LC rates. [11][12][13][14][15][16][17][18][19] The prolongation of the total treatment time may cause an accelerated repopulation effect, leading to a decrease in the LC rate of malignancies, such as head and neck, bladder, and cervical cancers. [20][21][22] Moreover, the split-course CRT strategy prolongs the treatment time and increases the time-economic cost of treatment; therefore, this treatment strategy is used primarily in patients who cannot tolerate therapy toxicity, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] but also in other patients [41][42][43][44][45][46][47][48][49][50][51][52] in an era when CRT techniques are commonly used.…”
Section: Split-course Crtmentioning
confidence: 99%
“…Complete and partial responses of 31 -92% were reported, representing an average of 50-55% response rate to sequential or simultaneous chemoradiation therapy in advanced lung cancer patients. Perez et a1 reported 50% local tumor control with radiation alone[21], while Emami et al[22] and Choi et al[23] had 59% and 76% tumor response (complete and partial) in unresectable lung cancer. Koning et al [I71 showed that weekly Cisplatin and RT did not improve local control or survival, but daily Cisplatin doses of 6 mg/m2 with RT provided statistically significant improvement in local control and 2 year survival.…”
mentioning
confidence: 99%